Inducing Selective Starvation of Cancer Cells through Synergistic Inhibition of glycolysis using Mannoheptulose and 2-Deoxy-D-Glucose - Ali Abd Allateef Al-Ali; Naeem Alkhammas, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2026)
The unique opportunity lies in targeting tumor cells through glycolysis, a pathway that compensates for decreased ATP production by increasing sugar consumption. This strategy allows for the development of a novel therapeutic approach, targeting malignant cells with selective pharmacological inhibitors of glycolysis without harming normal cells. In this study, hexokinase, glycolytic enzyme, was targeting to selectively inhibit energy production pathways in cancer cells without harming normal cells. The anticancer mechanisms of 2 Deoxy-D-Glucose (2DG) and Mannoheptulose (MH) in esophagus adenocarcinoma (SK-GT-4) and HBL-100 normal cell lines were investigated using MTT and wound healing assays to assess their cytotoxic effects and cellular proliferation. The apoptosis effect was detected using the AO/EB assay. To confirm the effect of agents on cell energy metabolism, the levels of ATP, pyruvate, and hexokinase were assessed as glycolysis parameters. The results showed significant cytotoxic effects of 2DG and MH on the growth of cancer cells, with a strong synergistic effect when used in combination, especially in SK-GT-4 cells. The IC50 values for 2DG and MH were 278 and 440 µg/mL, respectively, in SK-GT-4 cells, while HBL-100 cells did not reach IC50 values. Wound healing outcomes indicated a decrease in proliferation and invasion of cancer cells. Measurements of ATP and pyruvate levels showed that the combined use of the two drugs more effectively reduces cellular energy compared to using them independently, suggesting a synergistic effect against cancer cells and potential for a more effective treatment approach in the future